The evaluation of miscibility of blends of poly(ether imide) (Ultem®1000) and a copolyester of bisphenol-A with terephthalic and isophthalic acid (Ardel®D-100) by viscosimetry - Cakar, Fatih; Sakar, Dolunay; Cankurtaran, Ozlem; Karaman, Ferdane (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
The intermolecular interactions and miscibility behavior between poly(ether imide) (Ultem((R)) 1000) and a copolyester of bisphenol-A with a mixture of tereplithalic and isoplithalic acid (Ardel((R))D-100) in compositions of 100/0, 80/20, 60/40, 40/60, 20/80 and 0/100 have been investigated in dilute solutions in chloroform. An Ubbelohde-type home-made viscometer was used to determine the specific viscosities of the blends in a constant temperature bath. Several viscosity interaction parameters used as the criteria of miscibility were determined from viscosity measurements. The parameters suggested that Ultem((R)) 1000 and Arde((R))OD-100 were miscible. The miscibility of the polymers was confirmed by the results of differential scanning calorimetry measurements. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: miscibility; intrinsic viscosity; poly(ether imide); copolyester of bisphenol-A with terephthalic acid and isophthalic acid; DILUTE-SOLUTIONS; POLYMER; COMPATIBILITY; ACETATE); Polymer Science